Integrating Islamic Ethical Values to Improve Public Perception of NURTW Members in Ibadan Metropolis - Ridwan Olamilekan Mustapha (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2026)
Public perception of members of the National Union of Road Transport Workers (NURTW) in Nigeria has long been associated with negative stereotypes, including aggression, unprofessional conduct, and disruptive behavior in public spaces. Such perceptions have contributed to the stigmatization of the profession despite its significant role in the transportation sector and urban mobility. This study aims to examine prevailing public perceptions regarding the behavior and professionalism of NURTW members in Ibadan Metropolis and to explore how the integration of Islamic ethical values may contribute to improving their conduct and public image. The research employed a qualitative approach using Focus Group Discussions (FGDs) conducted with NURTW members in four major transport hubs in Ibadan: Ojoo Garage, Iwo Road Bus Terminal, Ajimobi Motor Park (Challenge), and the New Motor Park in Apata. Each FGD involved five participants who shared their experiences, perceptions, and views regarding professional conduct and ethical values. The findings reveal that although NURTW members are widely perceived as aggressive and unprofessional, many participants attributed such behaviors to work-related pressures, economic challenges, and the misconduct of a few individuals within the union. Importantly, participants expressed strong support for integrating Islamic ethical principles such as honesty, respect, accountability, and professionalism into their daily practices. The study concludes that structured ethical training, leadership commitment, and community engagement grounded in Islamic values could significantly improve the behavior of union members and reshape public perception of the profession. These findings highlight the potential of ethical frameworks in promoting professionalism within informal transportation sectors.